Peningkatan Kualitas Tri Dharma Perguruan Tinggi Melalui Pelatihan SISTER Pada STAI Ali bin Abi Thalib - Purnama Anaking; Yupit Sudianto; Helmy Widyantara (Politeknik Negeri Cilacap, 2024)
STAI Ali bin Abi Talib is one of the private Islamic universities in Surabaya. There are problems where changes in lecturer data (PDD) and others are still done manually in the form of physical files that are brought to Kopertais IV which oversees it. Whereas the Directorate General of Science and Technology Resources (SDID) of the Ministry of Research, Technology and Higher Education through circular letter at 2018 has provided direction on the implementation of the Integrated Resource Information System (SISTER) in public and private universiAties. To support this policy, universities need a special party or team to assist the application of technology so that the implementation of SISTER can run well, helping academic activities, data changes, and the tri dharma of lecturers in the future. Community service activities by the Telkom Institute of Technology Surabaya team at STAI Ali bin Abi Thalib were presented and carried out in six stages, starting from literature study, server configuration, preparation of presentation materials and training modules, SISTER application installation process, training, and evaluation. This activity resulted in the SISTER application installed on the STAI Ali bin Abi Thalib server which can be accessed online and also training that provides comprehensive knowledge, skills on the use of the SISTER application and debriefing with 10 video guides and 15 training modules for STAI Ali bin Thalib Surabaya.